PATTERNS OF DOMINANCE OF LANGUAGE VITALITIES AMONG MALAYSIAN STUDENTS IN PRIMARY NATIONAL-TYPE AND SECONDARY SCHOOLS - How, Soo Ying; Abdullah, Ain Nadzimah; Chan, Swee Heng (Indonesian Journal of Applied Linguistics, 2017)
Multilingualism is embedded in the Malaysian Education Blueprint (2015-2025) as a stated goal towards nation building. The education system provides opportunity to learn Malay which is the national language, the mother tongue (Mandarin or Tamil) and the English language as part of formal schooling. In fact, Malaysian primary schools are classified into two major divisions. Students can opt to study in national schools in which the medium of instruction is Malay with the provision for the learning of English and a mother tongue. The other option allows students to enrol in national-type schools of which the medium of instruction is either Mandarin or Tamil, with English and Malay taught as academic subjects. At secondary level, the medium of instruction in national schools is Malay and students are provided the opportunity to learn their mother tongue and English. Other than in school, other social milieus also allow the use and practice of these languages. Given this linguistic environment, there exists a myriad of language experiences within and outside formal learning which together would influence the totality of language vitality. This paper investigates language vitality featured in this multilingual environment. It focuses on the vitality of the English language among students that appears to co-exist with the learning and use of other languages as they progress through the primary and secondary levels. The vitality is measured by the following indicators: language preference, choice, dominance, use, attitude and motivation and proficiency which were used to develop a questionnaire to obtain data on strength evaluation of these languages. The methodology encompasses random and convenient sampling to obtain representative responses from students with different levels of education and language experiences. The study reveals relative vitalities of languages used and highlights values attached to languages at different points of language exposure that coincide with chronological age.